(untitled) (Communications in Mathematical Research, 2022)
In this paper, we give further results on the Drazin inverse of tensors via the Einstein product. We give a limit formula for the Drazin inverse of tensors. By using this formula, the representations for the Drazin inverse of several block tensor are obtained. Further, we give the Drazin inverse of the sum of two tensors based on the representation for the Drazin inverse of a block tensor.